Proceso civilizatorio, dialéctica congelada y emocionesdel estatus. Sobre Walter Benjamin y Norbert Elías - Ramírez Lamus, Sergio (Sociedad y Economía, 2004)
Walter Benjamin’s notion of history seems to have some affinities with that of Norbert Elias. Nevertheless, a close scrutiny of Elias’ process of civilization shows that it is at odds with Benjamin’s theleological perspective, in spite of some affinities found between the notion of monad (Benjamin) and figuration (Elias). On the other hand, the critique of historicist empathy common to both authors does not hold when they approach the s ocio-historicity of emotions.